Ground reaction forces and kinematics of plant leg position during instep kicking in male and female collegiate soccer players - Orloff, H.; Sumida, B.; Chow, J.; Habibi, L.; Fujino, A.; Kramer, H. B. (Sports Biomechanics, 2008)
The players' ability to achieve the greatest distance in kicking is determined by their efficiency in transferring kinetic energy from the body to the ball. The purpose of this study was to compare the kinetics and kinematics of the plant leg position between male and female collegiate soccer players during instep kicking. Twenty-three soccer players (11 males and 12 females) were filmed in both the sagittal and posterior views while performing a maximal instep kick. Plant leg kinetic data were also collected using an AMTI 1000 force platform. There were no significant differences between the sexes in plant leg position, but females had significantly greater trunk lean, plant leg angle, and medial-lateral ground reaction force than the males. Males showed higher vertical ground reaction forces at ball contact, but there were no significant differences in ball speed at take-off between the sexes. Ball speed at take-off was inversely related to peak anterior-posterior ground reaction force ( - 0.65). The anatomical differences between the sexes were reflected in greater trunk lean and lower leg angle in the females.